Thermo-Mechanical Behaviour of Schizostachyum Grande Bamboo Fibre, Epoxy and Vinyl Resin Thermoset for Potential in Composite Application - Md Desa, Mohd Shaffiq; Wan Jusoh, Wan Amizah; Syed Zin, Syed Mohd Fareed; Che Rosely, Noor Ain Najihah; Loke, Kok Foong (Journal of Advanced Industrial Technology and Application, 2025)
This study was conducted to investigate bamboo fibre and thermoset resin’s thermophology and thermoset resin for composite applications and to delve into the morphology, behaviour, and mechanical properties of bamboo fibres from the species Schizostachyum grande, as well as thermoset resins such as vinyl and epoxy. Besides, fibre and thermoset resins were incorporated to achieve the desired mechanical properties, specifically for tensile strength and elongation characteristics. Additionally, this study was also conducted to determine physical and chemical composition properties, where Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) tests were executed on bamboo fibre and epoxy and vinyl resins. Furthermore, Thermogravimetric Analysis (TGA) and Fourier Transform Infrared Spectroscopy (FTIR) tests were performed to determine the physical performance of the material in terms of mass loss over time. The data obtained for bamboo fibre, epoxy, and vinyl resin were then compared for the factors of maximum stress, stiffness, deflection, and maximum load. Hence, this research contributes to the understanding of bamboo fibres and thermoset suitability for sustainable engineering applications by providing comprehensive data on morphology, behavior, and tensile properties. The results of this research are useful in terms of design and materials selection processes, enabling the creation of more robust and ecologically friendly engineering solutions for the chosen fibre and thermoset resin towards sustainable structures, such as modular houses.